1991
DOI: 10.1093/oxfordjournals.humrep.a137312
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the late proliferative phase endometrium by ultrasonography in patients undergoing in-vitro fertilization and embryo transfer (IVF/ET)

Abstract: This study reports on 330 women aged 29 to 45 years, who underwent 411 cycles of in-vitro fertilization and embryo transfer (IVF/ET). Vaginal sonograms were performed during the late proliferative phase of natural cycles and cycles of controlled ovarian hyperstimulation (COH) with gonadotrophins, to evaluate both the thickness and echogenicity of the endometrium. Findings classified as Grade I; characterized by homogeneous echogenicity of the endometrium, and Grade II; characterized by an outer peripheral laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(77 citation statements)
references
References 0 publications
7
65
1
4
Order By: Relevance
“…A thin endometrium it has been reported in 5 % of women <40 years of age and in 25 % of 41-45 years old women [18] and it has also been related to poor pregnancy outcome [20]. Regarding the etiology it is considered mainly idiopathic, however, a surgical complication postcurettage might be identified in some cases [19].…”
Section: Introductionmentioning
confidence: 99%
“…A thin endometrium it has been reported in 5 % of women <40 years of age and in 25 % of 41-45 years old women [18] and it has also been related to poor pregnancy outcome [20]. Regarding the etiology it is considered mainly idiopathic, however, a surgical complication postcurettage might be identified in some cases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of quite a few published studies, the prognostic value of ultrasonographic endometrial thickness measurements (and other parameters) in predicting implantation and pregnancy rates remains controversial. Some investigators have demonstrated a positive correlation between endometrial thickness and pregnancy rates [1][2][3][4][5][6][7][8]11] while others have not found such an association [9,10,[12][13][14], or only in association with other parameters [15,16]. However, these differences may be in part attributed to different patient populations, stimulation protocols used or measurement timing.…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences may be in part attributed to different patient populations, stimulation protocols used or measurement timing. The incidence of thin endometrium in natural cycles has been reported to be 5% in women <40 years of age and 25% in 41 to 45 years old women [6]. The etiology of unresponsive endometrium and its impact on ART outcome have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results coincided with previous researchers who showed a correlation between the endometrium pattern and IVF success. Sher et al (35) showed that the endometrial pattern has been correlated with IVF success rates, with a trilaminar pattern shown to be more favourable than a homogenous luteal pattern at the time of the human chorionic gonadotrophin administration. Singh et al (33) showed that the triple -line pattern of the endometrium was good prognostic factor for the occurrence of pregnancy.…”
Section: Such Finding Coincided With Silverberg Et Almentioning
confidence: 99%